Communication in a web-based conferencing system: the quality of computer-mediated interactions - Angeli, Charoula; Valanides, Nicos; Bonk, Curtis J. (British journal of educational technology, 2003)
Time constraints and teaching in crowded classrooms restrict in‐depth dialogical interaction in teaching and learning. Electronic conferencing systems, however, have the potential to foster online discussions beyond class time. Case‐based instruction also constitutes a promising approach in fostering learners' participation and reflection. The purpose of this study was to investigate (a) the extent to which an electronic conferencing system, named COW (“Conferencing on the Web”), facilitates pre‐service teachers' communication outside their classroom, when discussing teaching cases from their field experiences, and (b) the potential of COW and case‐based instruction to foster quality discourse and promote students' critical‐thinking skills. The results showed that students' online discourse was mostly an exchange of personal experiences and did not reflect well‐supported reasoning. Future research on the issue of interactivity should address motivational and affective variables related to the implementation of distance‐education methods, variations in pedagogical activity and task structure, and the readiness of mentors and learners.